Role of the Bone Marrow Niche in Supporting the Pathogenesis of Lymphoid Malignancies - Jalali, Shahrzad; Ansell, Stephen M. (Frontiers in Cell and Developmental Biology, 2021)
While the bone marrow (BM) microenvironment is the primary location for nurturing the multipotent hematopoietic stem cells and developing the blood cells of either myeloid or lymphoid origin under normal physiological conditions, it could provide a supportive milieu for the proliferation of blood cancer cells. In fact, the multiple and complex direct cell-to-cell or indirect soluble factors-mediated interactions taking place among the BM cells of different origins are shown to play a significant role in tumorigenesis of hematological cancers. In the current review, we focus on lymphoid malignancies and highlight the novel insights surrounding the role of both cellular as well as non-cellular BM compartments in modulating hematopoiesis and promoting growth and proliferation of cancer cells across a variety of aggressive and indolent lymphoid malignancies, including diffuse large B-cell lymphoma, follicular lymphoma, mantle cell lymphoma, and Waldenstrom Macroglobulinemia. We also discuss the mechanisms of potential intervention and discuss their therapeutic impact in clinical settings.